Aerogel-based heat-preservation, heat-insulation and waterproof composite coating material for building outer wall and preparation method thereof

By introducing a variety of functional fillers and modified materials into the exterior wall coating of building, the composite coating system is constructed, which solves the brittleness and hygroscopicity of aerogels in the exterior wall applications, and achieves excellent thermal insulation, waterproofing and durability of the coating.

CN119842297AInactive Publication Date: 2025-04-18HEFEI YOUTAI BUILDING MATERIALS CO LTD

Patent Information

Application Number
CN202510139983.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Aerogels have problems of high brittleness and strong hygroscopicity in building exterior wall applications, which affects their thermal insulation performance and structural stability.

Method used

A composite coating system is constructed by hydrophobically modified silica aerogel, modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and graphene oxide composite modified boron nitride nanosheets.

Benefits of technology

It significantly improves the heat insulation, waterproof, wear resistance and long-term stability of the coating, solves the brittleness and hygroscopicity of the aerogel, and improves the overall performance of the building exterior wall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842297A_ABST
    Figure CN119842297A_ABST
Patent Text Reader

Abstract

The invention provides an aerogel-based heat-preservation, heat-insulation and waterproof composite coating material for a building outer wall and a preparation method thereof, and belongs to the field of building materials. Through hydrophobic modified silicon dioxide aerogel, a lightweight heat insulation frame is provided, and the waterproofness and compatibility are improved; the mechanical property and the crack resistance are enhanced through the modified potassium titanate nanofibers, and self-adaptive heat insulation is achieved; the thermoelectric effect, the wear resistance and the thermal regulation performance are optimized through plasma treatment and polyaniline coated tungsten carbide nanoparticles; the heat management performance, the crack resistance and the comprehensive heat insulation and waterproof capacity are improved through graphene oxide composite modified boron nitride; the flexibility, the hydrophobicity and the interfacial compatibility are improved through organic silicon modified bisphenol A epoxy resin; and the performance of the coating is optimized through the synergistic effect of the components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and relates to an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof. Background Art

[0002] Aerogel is a material with great potential, known for its high porosity and light weight, so it is vividly called "solid smoke". The uniqueness of this material lies in its microstructure, with a huge specific surface area and tiny pores, which enables it to show excellent performance in a variety of applications. Especially in terms of thermal insulation, aerogel has extremely low thermal conductivity and can effectively prevent heat transfer, which makes aerogel an important innovative material in the field of building energy conservation.

[0003] In the application of building exterior walls, aerogel can not only significantly reduce heat conduction, but also improve the overall comfort and energy efficiency level of the building by reducing energy consumption. Compared with traditional insulation materials, aerogel can achieve the same or even better insulation effect at a thinner layer thickness, thus providing architects with greater flexibility and creative space. In addition, the lightweight properties of aerogel make it more convenient in installation and construction, reducing the burden on the building structure, and is especially suitable for high-rise buildings and energy-saving renovation projects.

[0004] Although aerogels have shown significant advantages in thermal insulation, they still face some challenges and limitations in practical applications. First, aerogels are highly brittle, which means that aerogels are prone to breakage during construction or when the external environment changes, thus affecting their thermal insulation performance and the stability of the overall structure. Second, the hygroscopicity of aerogels is another problem that needs to be solved. In a humid environment, aerogels easily absorb water, which not only leads to a decrease in their thermal insulation performance, but may also cause quality problems such as mildew, further affecting the service life of the building and the health of the living environment. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof. The present invention constructs a composite coating system with excellent comprehensive performance by introducing a variety of functional fillers such as hydrophobic modified silica aerogel, modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and graphene oxide composite modified boron nitride nanosheets, and organosilicon-modified bisphenol A epoxy resin as a matrix. Silica aerogel provides a lightweight insulation frame and improves waterproofness, potassium titanate nanofibers enhance mechanical properties and crack resistance, tungsten carbide optimizes thermal regulation ability and long-term stability through thermoelectric effect and wear resistance, and boron nitride improves thermal management performance and crack resistance through a two-dimensional sheet structure. At the same time, the synergistic effect between the fillers realizes the comprehensive optimization of thermal management, thermal insulation, waterproof and weather resistance. The organosilicon-modified epoxy resin provides high strength, flexibility and excellent interface compatibility with inorganic fillers, so that the coating exhibits excellent thermal insulation, waterproof, wear resistance and long-term stability in harsh environments.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls, the method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls comprising:

[0008] S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder;

[0009] S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers;

[0010] S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles;

[0011] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets;

[0012] S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution, adding γ-aminopropyl polydimethylsiloxane to obtain a reaction solution J, reacting under nitrogen protection, then adding tetrahydrofuran to obtain a solution K, and rotary evaporating to obtain a silicone-modified epoxy resin;

[0013] S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

[0014] Specifically, the preparation method of the aerogel-based thermal insulation and waterproof composite coating material for building exterior walls comprises:

[0015] S1: TEOS and anhydrous ethanol are mixed, deionized water and ammonia water are added to obtain solution A, the mixture is stirred at room temperature and then heated, a mixed modifier is added dropwise to obtain reaction solution B, the mixture is stirred and reacted, and then aged at room temperature to obtain a gel, and the hydrophobically modified silica aerogel is obtained by supercritical drying after alcohol gel exchange, and the modified silica aerogel powder is obtained by pulverization;

[0016] S2: Mix potassium titanate nanofibers with Tris buffer, add dopamine hydrochloride to obtain reaction solution C, stir at room temperature, filter and wash to obtain precipitate D, disperse it in deionized water, add polyacrylic acid aqueous solution to obtain reaction solution E, stir the reaction at constant temperature, centrifuge and vacuum dry to obtain modified potassium titanate;

[0017] S3: treating tungsten carbide nanoparticles in a plasma device to obtain activated tungsten carbide nanoparticles, dispersing the activated tungsten carbide nanoparticles in a hydrochloric acid solution, adding aniline under ice bath conditions to obtain a reaction solution F, adding an ammonium persulfate solution dropwise after stirring to obtain a reaction solution G, reacting at low temperature, centrifuging, washing, and vacuum drying to obtain modified tungsten carbide;

[0018] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride nanosheets, mixing the activated boron nitride nanosheet / N,N-dimethylformamide dispersion with the graphene oxide dispersion to obtain a reaction solution H, adding ascorbic acid to obtain a reaction solution I, reacting in a constant temperature water bath, filtering, washing, and vacuum drying to obtain modified boron nitride;

[0019] S5: mixing bisphenol A epoxy resin and toluene / tetrahydrofuran mixed solution to obtain a resin dispersion, adding γ-aminopropyl polydimethylsiloxane / toluene solution after stirring to obtain a reaction solution J, stirring under nitrogen protection at a constant temperature and then cooling to room temperature, then adding tetrahydrofuran to dilute to obtain a solution K, filtering and rotary evaporating to obtain a silicone-modified epoxy resin;

[0020] S6: Dispersing modified potassium titanate, modified tungsten carbide and modified boron nitride in anhydrous ethanol and mixing them evenly, adding organosilicon-modified epoxy resin to obtain a base liquid, adding modified silica aerogel powder after high-speed dispersion, and then adding carbon fiber and additives to obtain a pre-treated coating liquid, and adding a curing agent after vacuum degassing to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls;

[0021] As a preferred technical solution of the present invention, in step S1, the volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:3-4, for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional embodiments, the molar ratio of deionized water to tetraethyl orthosilicate is 2-3:1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional embodiments, the concentration of the ammonia water is 0.2-0.3M, for example, it can be 0.20M, 0.21M, 0.22M, 0.23M, 0.24M, 0.25M, 0.26M, 0.27M, 0.28M, 0.29M or 0.30M, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional embodiments, the adding of ammonia water to the solution pH to 8-9, for example, can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional embodiments, the stirring reaction time of solution A at room temperature is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional embodiments, the solution A is stirred and reacted at room temperature and then heated to 45-50°C, for example, 45.0°C, 45.5°C, 46.0°C, 46.5°C, 47.0°C, 47.5°C, 48.0°C, 48.5°C, 49.0°C, 49.5°C or 50.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional embodiments, the dripping rate of the mixed modifier is 1-2 mL / min, for example, it can be 1.0 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min or 2.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional embodiments, the volume ratio of hexamethyldisilazide / chloromethyltrimethylsilane in the mixed modifier is 1-2:1, for example, it can be 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional embodiments, the molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.2-0.3:1, for example, it can be 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1 or 0.30:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional embodiments, the stirring reaction time of the reaction liquid B is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional embodiments, the aging time of the reaction solution B at room temperature after stirring the reaction is 24-48h, for example, it can be 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h or 48h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] As a preferred technical solution of the present invention, in step S2, the mass ratio of the potassium titanate nanofibers to the Tris buffer is 1:200-250, for example, it can be 1:200, 1:205, 1:210, 1:215, 1:220, 1:225, 1:230, 1:235, 1:240, 1:245 or 1:250, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional embodiments, the mass ratio of the potassium titanate nanofibers to dopamine hydrochloride is 2.5-3:1, for example, it can be 2.5:1, 2.55:1, 2.6:1, 2.65:1, 2.7:1, 2.75:1, 2.8:1, 2.85:1, 2.9:1, 2.95:1 or 3.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional embodiments, the reaction solution C is stirred at room temperature for 5-6 hours, for example, 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional embodiments, the mass fraction of the polyacrylic acid aqueous solution is 5-6wt.%, for example, it can be 5.0wt.%, 5.1wt.%, 5.2wt.%, 5.3wt.%, 5.4wt.%, 5.5wt.%, 5.6wt.%, 5.7wt.%, 5.8wt.%, 5.9wt.% or 6.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional embodiments, the mass ratio of the polyacrylic acid to the precipitate D is 0.3-0.4:1, for example, it can be 0.3:1, 0.31:1, 0.32:1, 0.33:1, 0.34:1, 0.35:1, 0.36:1, 0.37:1, 0.38:1, 0.39:1 or 0.4:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional embodiments, the constant temperature stirring reaction temperature of the reaction liquid E is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional embodiments, the constant temperature stirring reaction time of the reaction liquid E is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] As a preferred technical solution of the present invention, in step S3, the concentration of the hydrochloric acid solution is 1-2M, for example, it can be 1.0M, 1.1M, 1.2M, 1.3M, 1.4M, 1.5M, 1.6M, 1.7M, 1.8M, 1.9M or 2.0M, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional embodiments, the mass ratio of the activated tungsten carbide nanoparticles to the hydrochloric acid solution is 1:200-250, for example, it can be 1:200, 1:205, 1:210, 1:215, 1:220, 1:225, 1:230, 1:235, 1:240, 1:245 or 1:250, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional embodiments, the mass ratio of the activated tungsten carbide nanoparticles to aniline is 2-2.5:1, for example, it can be 2.0:1, 2.05:1, 2.10:1, 2.15:1, 2.20:1, 2.25:1, 2.30:1, 2.35:1, 2.40:1, 2.45:1 or 2.5:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional embodiments, the concentration of the ammonium persulfate solution is 1-2M, for example, it can be 1.0M, 1.1M, 1.2M, 1.3M, 1.4M, 1.5M, 1.6M, 1.7M, 1.8M, 1.9M or 2.0M, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional embodiments, the molar ratio of ammonium persulfate to aniline is 1.2-1.4:1, for example, it can be 1.2:1, 1.22:1, 1.24:1, 1.26:1, 1.28:1, 1.3:1, 1.32:1, 1.34:1, 1.36:1, 1.38:1 or 1.4:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional embodiments, the dropping speed of the ammonium persulfate solution is 1-2 mL / min, for example, it can be 1.0 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min or 2.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional embodiments, the temperature of the low-temperature reaction of the reaction liquid G is 0-5°C, for example, it can be 0°C, 0.5°C, 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C or 5°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional embodiments, the low-temperature reaction time of the reaction liquid G is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] As a preferred technical solution of the present invention, in step S4, the mass ratio of the activated boron nitride nanosheets / N,N-dimethylformamide dispersion is 1:150-200, for example, it can be 1:150, 1:155, 1:160, 1:165, 1:170, 1:175, 1:180, 1:185, 1:190, 1:195 or 1:200, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional embodiments, the concentration of the graphene oxide dispersion is 2-3 mg / mL, for example, it can be 2.0 mg / mL, 2.1 mg / mL, 2.2 mg / mL, 2.3 mg / mL, 2.4 mg / mL, 2.5 mg / mL, 2.6 mg / mL, 2.7 mg / mL, 2.8 mg / mL, 2.9 mg / mL or 3.0 mg / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional embodiments, the mass ratio of the graphene oxide to the activated boron nitride nanosheets is 0.2-0.3:1, for example, it can be 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1 or 0.30:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional embodiments, the mass ratio of graphene oxide to ascorbic acid is 1:3-4, for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional embodiments, the temperature of the constant temperature water bath reaction of the reaction solution I is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional embodiments, the constant temperature water bath reaction time of the reaction solution I is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] As a preferred technical solution of the present invention, in step S5, the volume ratio of toluene to tetrahydrofuran in the toluene / tetrahydrofuran mixed solution is 3-4:1, for example, it can be 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1 or 4:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional embodiments, the mass fraction of the bisphenol A epoxy resin in the resin dispersion is 40-50wt.%, for example, it can be 40wt.%, 41wt.%, 42wt.%, 43wt.%, 44wt.%, 45wt.%, 46wt.%, 47wt.%, 48wt.%, 49wt.% or 50wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional embodiments, the molar ratio of the bisphenol A epoxy resin to γ-aminopropyl polydimethylsiloxane is 2-3:1, for example, it can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional embodiments, the mass fraction of the γ-aminopropyl polydimethylsiloxane / toluene solution is 30-40wt.%, for example, it can be 30wt.%, 31wt.%, 32wt.%, 33wt.%, 34wt.%, 35wt.%, 36wt.%, 37wt.%, 38wt.%, 39wt.% or 40wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional embodiments, the temperature of the constant temperature reaction of the reaction liquid J is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional embodiments, the constant temperature reaction time of the reaction liquid J is 3-4h, for example, it can be 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional embodiments, the mass fraction of tetrahydrofuran in the solution K is 30-35wt.%, for example, it can be 30wt.%, 31wt.%, 32wt.%, 33wt.%, 34wt.% or 35wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] As a preferred technical solution of the present invention, in step S6, the mass ratio of the mixture of modified potassium titanate, modified tungsten carbide, and modified boron nitride to ethanol is 1:40-50, for example, it can be 1:40, 1:41, 1:42, 1:43, 1:44, 1:45, 1:46, 1:47, 1:48, 1:49 or 1:50, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional embodiments, the rotation speed of the high-speed dispersion of the base liquid is 3000-4000rpm, for example, it can be 3000rpm, 3100rpm, 3200rpm, 3300rpm, 3400rpm, 3500rpm, 3600rpm, 3700rpm, 3800rpm, 3900rpm or 4000rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional embodiments, the time for high-speed dispersion of the base liquid is 20-30 min, for example, it can be 20.0 min, 21.0 min, 22.0 min, 23.0 min, 24.0 min, 25.0 min, 26.0 min, 27.0 min, 28.0 min, 29.0 min or 30.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In a second aspect, the present invention provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls. The aerogel-based thermal insulation and waterproof composite coating material for building exterior walls comprises modified potassium titanate, modified tungsten carbide, modified boron nitride, organosilicon-modified epoxy resin, modified silica aerogel powder, carbon fiber, additives and curing agent.

[0064] Silica aerogel is introduced as a base material in the present invention. Silica aerogel is a porous material formed by cross-linking silica nanoparticles through a three-dimensional network. The pore size is mainly in the nanometer range and has an extremely high specific surface area. The nanoporous structure of silica aerogel effectively blocks solid conduction and gas conduction in heat conduction, and significantly inhibits convective heat transfer at a microscopic scale, thereby showing extremely low thermal conductivity, and is one of the excellent solid thermal insulation materials. In addition, its low density makes it very lightweight, meeting the demand for lightweight building exterior walls.

[0065] However, although the nanoporous structure of aerogel provides excellent thermal insulation performance, it also leads to poor mechanical properties, showing greater brittleness and fragility. In addition, the surface of untreated silica is rich in hydrophilic hydroxyl groups, which easily absorbs moisture, thereby significantly increasing the overall thermal conductivity of the material and causing a decrease in thermal insulation performance. Therefore, the present invention introduces hydrophobic groups to silanize the surface of aerogel to enhance its waterproofness and reduce its hygroscopicity.

[0066] The hydrophobically modified aerogel is more compatible with silicone-modified epoxy resin, and its surface active groups can form chemical or physical bonds with the resin matrix, reduce interface defects, improve dispersibility, and enhance the durability and overall mechanical properties of the coating. In addition, the synergistic effect with other reinforcing materials (such as potassium titanate nanofibers and tungsten carbide particles) further optimizes the comprehensive performance of the coating, making it have excellent thermal insulation, waterproof and weather resistance.

[0067] Potassium titanate is introduced as an inorganic functional filler in the present invention. Potassium titanate is a titanate material in the form of nanofibers with a high aspect ratio and a large specific surface area. The fibrous structure can form a support network in the coating, significantly improving the mechanical properties and crack resistance of the coating; secondly, potassium titanate has excellent mechanical strength, heat resistance and chemical stability, and is suitable for building exterior wall applications under harsh climatic conditions; in addition, the surface of potassium titanate is rich in active sites, which facilitates the introduction of functional groups through chemical modification to enhance the binding force with the organic matrix. Potassium titanate has a tunnel-like crystal structure, the Ti-O skeleton forms a stable framework, and the K + Ions are located in the tunnels to balance the charges. This tunnel-like structure gives potassium titanate good ion migration and ion exchange properties.

[0068] When there is a temperature gradient, K at the high temperature end + The more heat energy is obtained, the more intense the vibration of the ions is, until they overcome the potential barrier and begin to migrate, resulting in an increase in ion mobility, K + Ions migrate to the low temperature area, leaving a negative charge area in the high temperature area, and forming a positive charge negative pole in the low temperature area. The migration of ions causes the separation of positive and negative charges, forming a local electric field; the local electric field can regulate the propagation path and scattering behavior of phonons (the dominant heat transfer carrier in non-metallic materials), thereby changing the local energy distribution. When the ion concentration gradient and the electric field strength reach a balance, a stable thermal barrier layer can be formed. When the temperature changes, it affects the ion migration rate, and the electric field strength is also adjusted accordingly, thereby achieving adaptive thermal insulation.

[0069] However, the interfacial bonding ability of unmodified potassium titanate with organic matrices such as epoxy resin is weak, and the fibrous structure is easy to agglomerate, which may lead to uneven dispersion. Therefore, dopamine hydrochloride and polyacrylic acid are introduced to modify potassium titanate. Dopamine can form a bionic coating on the surface of potassium titanate to improve its hydrophilicity and dispersibility; polyacrylic acid further enhances its dispersion stability through electrostatic action and improves its bonding with the matrix. The active surface of the modified potassium titanate can better combine with the resin matrix to form a strong interface, thereby improving the strength and toughness of the coating. At the same time, potassium titanate can synergize with silica aerogel to enhance the overall mechanical properties of the coating by filling the porous structure of the aerogel.

[0070] Tungsten carbide is introduced as a functional filler in the present invention. Tungsten carbide is a hard material with high hardness, high density and chemical stability, making it an important component for modifying the wear resistance of the coating, and is suitable for building exterior walls exposed to erosion environments such as wind, sand and rain for a long time. The characteristics of nanoparticles significantly increase the specific surface area, and tungsten carbide exhibits excellent stability at high temperatures, which can improve the heat resistance and long-term weather resistance of the coating.

[0071] Tungsten carbide nanoparticles have certain thermoelectric properties. When there is a temperature gradient, the distribution of electrons and holes inside them changes, resulting in a thermoelectric potential difference between the particles. In the aerogel network, tungsten carbide particles exist in the form of dispersed "thermoelectric points" and work together with the aerogel skeleton to form a discontinuous thermoelectric path. Through this mechanism, the conversion of part of the thermal energy and the optimization of the local heat flow path can effectively reduce the proportion of direct heat conduction, thereby improving the thermal insulation performance of the coating. This effect is particularly significant under high temperature gradients and helps to form an adaptive thermal regulation system.

[0072] However, the surface activity of unmodified tungsten carbide is low, and it is not easy to form a strong interface with the organic matrix. At the same time, the particles are easy to agglomerate, which affects the uniformity of the coating. To this end, the surface of tungsten carbide particles is modified by plasma treatment, and active sites are introduced on its surface, which significantly improves the dispersibility and interfacial bonding of the particles. Further, polyaniline coating is used to enhance the dispersion stability of the particles by utilizing its long-chain molecular structure and electrostatic effect, while giving the particles a certain conductivity, further reducing the agglomeration phenomenon and enhancing the thermoelectric effect.

[0073] The modified tungsten carbide can not only significantly enhance the wear resistance of the coating, but also fill the porous structure through the synergistic effect with the aerogel, thereby improving the mechanical strength and impact resistance of the coating. In addition, the interface bonding with the modified epoxy resin matrix also further optimizes the uniformity and comprehensive performance of the coating, making it have excellent wear resistance, thermal insulation and long-term stability.

[0074] Boron nitride nanosheets are introduced as functional fillers in the present invention. Boron nitride is a hexagonal crystal structure material with two-dimensional sheet characteristics similar to graphene, and its sheets are bonded by weak van der Waals forces. Boron nitride has extremely high thermal conductivity in the direction parallel to the sheets, while the thermal conductivity in the vertical direction is low. This anisotropic thermal conductivity behavior makes it an ideal thermal conductivity regulator. Boron nitride nanosheets can form a dispersed barrier layer in the coating, which significantly reduces the effective thermal conductivity of the coating by extending the heat conduction path and enhancing phonon scattering, thereby achieving excellent thermal insulation performance.

[0075] In addition, hexagonal boron nitride also has piezoelectricity derived from its non-centrosymmetric crystal structure. When the temperature gradient causes thermal stress, the boron nitride lattice undergoes a slight deformation, and its BN bond polarity is enhanced, resulting in charge accumulation on both sides of the material and the formation of an electric dipole moment. The local electric field generated by the piezoelectric effect can enhance the scattering effect of phonons through electro-acoustic coupling, thereby further extending the heat transfer path and reducing the effective thermal conductivity of the coating. At the same time, under the action of the local electric field, the silica aerogel skeleton may be polarized to form an ordered dipole moment arrangement, generating an additional scattering layer at the interface, further increasing the thermal impedance.

[0076] However, unmodified boron nitride is easily reunited due to the surface chemical inertness and strong inter-sheet van der Waals force, and the interface bonding with the organic matrix is ​​weak, which affects the uniformity and comprehensive performance of the coating. For this reason, the present invention introduces more functional sites by compounding boron nitride with graphene oxide and utilizing the oxygen-containing groups on the surface of graphene oxide. These active groups can enhance the interfacial bonding force of boron nitride and epoxy resin matrix by electrostatic action or chemical bonding, and simultaneously weaken the van der Waals force between the boron nitride sheets, thereby significantly improving its dispersion stability.

[0077] The modified boron nitride can not only be evenly distributed in the composite coating and optimize the thermal management performance of the coating through its two-dimensional structure and piezoelectric effect, but also enhance the mechanical properties and crack resistance of the coating, making it exhibit excellent comprehensive performance in thermal insulation, waterproofness and durability.

[0078] In the present invention, bisphenol A epoxy resin is selected as the main binder of the coating to provide overall strength and adhesion. Bisphenol A epoxy resin reacts with a curing agent through its epoxy group to form a three-dimensional network structure with a high degree of crosslinking. The crosslinked epoxy resin has excellent mechanical strength, adhesion and chemical corrosion resistance, but due to its highly crosslinked molecular structure, the flexibility of the molecular chain is significantly reduced, showing greater brittleness and poor impact resistance.

[0079] To solve this problem, the present invention introduces flexible silicon-oxygen bonds into the resin molecular chain by introducing silicone-modified epoxy resin. Silicon-oxygen bonds have lower bond energy and longer bond length, giving the molecular chain greater rotational freedom, thereby significantly improving the flexibility of epoxy resin. In addition, the low surface energy characteristics of silicone further enhance the hydrophobicity of epoxy resin and reduce the risk of coating cracking. The modified epoxy resin exhibits significant flexibility and hydrophobicity, wherein flexibility enables the coating to effectively absorb and disperse energy under external stress, avoiding the generation or expansion of cracks caused by local stress concentration; and hydrophobicity reduces the adsorption of moisture in the environment by the coating, thereby reducing the risk of stress concentration and material degradation caused by moisture intrusion.

[0080] In addition, the modified epoxy resin not only provides high strength and flexibility, but also provides a stable bonding platform for the organic-inorganic composite material in the coating. After the introduction of silicone, the epoxy resin exhibits better interfacial compatibility and can form a stronger interfacial bond with inorganic fillers (such as aerogel, boron nitride, tungsten carbide, etc.), thereby significantly improving the mechanical properties, thermal management properties and long-term stability of the composite coating.

[0081] There is a significant synergistic effect in the coating system of the present invention: the low thermal conductivity of silica aerogel, the high thermal conductivity of boron nitride and the thermal conductivity regulation of tungsten carbide jointly optimize the thermal management performance of the coating. Silica aerogel is a low-density nanoporous material, and its low thermal conductivity comes from the inhibition of solid heat conduction by the aerogel network, the limitation of gas heat conduction by pores, and the absorption and scattering of infrared thermal radiation. In the coating, the aerogel is evenly distributed as a matrix material to form an overall thermal insulation frame, which effectively reduces the overall thermal conductivity of the coating and prevents the external high or low temperature from being transmitted to the interior of the building.

[0082] Boron nitride is a two-dimensional sheet material. Its high thermal conductivity parallel to the sheet direction can avoid local overheating through rapid heat diffusion, thereby achieving thermal uniformity. In the coating, boron nitride is dispersed in the form of filler, and through its efficient heat transfer path in the sheet direction, it diffuses local heat from the "hot spot" area to the surrounding area, effectively optimizing the temperature distribution of the coating.

[0083] As a regulating material, tungsten carbide regulates the heat flow path through its filling effect and unique thermoelectric effect, further homogenizing the heat flow distribution in the coating. Tungsten carbide particles are dispersed in the coating to form a "local heat conduction channel" that can dynamically optimize the heat flow path under high temperature gradients, thereby improving the overall thermal management performance of the coating.

[0084] Through the synergistic combination of the aerogel's thermal insulation frame, boron nitride's efficient heat conduction path, and tungsten carbide's heat flow regulation, the coating system has successfully achieved multiple optimizations of thermal management performance, which can not only significantly inhibit heat transfer, but also quickly diffuse local heat, thereby giving the building wall an excellent thermal insulation effect.

[0085] Compared with the prior art, the present invention has the following beneficial effects:

[0086] (1) The present invention introduces hydrophobically modified silica aerogel as a base material, not only utilizing its nanoporous structure to provide excellent thermal insulation performance, but also enhancing the waterproofness and compatibility with the resin matrix through silanization modification, while synergizing with other reinforcing materials to improve the thermal insulation, waterproofness and weather resistance of the coating;

[0087] (2) The present invention introduces modified potassium titanate nanofibers as inorganic functional fillers, utilizes their fibrous structure and tunnel-like crystal structure to enhance the mechanical properties and crack resistance of the coating, and realizes adaptive thermal insulation through the ion migration effect; and improves its dispersibility and bonding strength with the resin matrix through modification with dopamine hydrochloride and polyacrylic acid, and synergizes with silica aerogel to further optimize the mechanical properties and thermal insulation properties of the coating;

[0088] (3) The present invention modifies tungsten carbide nanoparticles by plasma treatment and polyaniline coating to enhance their dispersibility, interfacial bonding strength and thermoelectric effect. The high hardness and thermoelectric properties of the tungsten carbide nanoparticles are used to significantly improve the wear resistance, thermal insulation and adaptive thermal regulation of the coating. The tungsten carbide nanoparticles are used in synergy with aerogel to enhance the mechanical properties and long-term stability of the coating. The tungsten carbide nanoparticles are suitable for the harsh environment of building exterior walls.

[0089] (4) The present invention uses graphene oxide to compositely modify boron nitride nanosheets to improve their dispersibility and interfacial bonding strength, and utilizes the two-dimensional sheet structure, anisotropic thermal conductivity and piezoelectric effect of boron nitride to significantly optimize the thermal management performance of the coating, and through the synergistic effect with aerogel, improves the mechanical properties, crack resistance and comprehensive thermal insulation, waterproofness and durability of the coating;

[0090] (5) The present invention introduces flexible silicon-oxygen bonds into the organosilicon-modified bisphenol A epoxy resin to significantly improve its flexibility and hydrophobicity, while enhancing the interfacial compatibility with the inorganic filler, thereby optimizing the mechanical properties, thermal management properties and long-term stability of the composite coating while providing high strength and adhesion;

[0091] (6) The low thermal conductivity of silica aerogel, the efficient thermal diffusion characteristics of boron nitride, and the heat flow regulation effect of tungsten carbide synergistically optimize the thermal management performance of the coating, achieving an organic combination of the insulation frame, heat conduction path, and heat flow homogenization, so that the coating can both inhibit heat transfer and quickly diffuse local heat, thereby giving the building wall an excellent thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0092] Figure 1 This is a scanning electron microscope image of the modified silica aerogel powder provided in Example 1 of the present invention;

[0093] Figure 2 A high-resolution transmission electron microscopy image of the modified tungsten carbide provided in Example 1 of the present invention;

[0094] Figure 3 This is a scanning electron microscope image of the modified boron nitride provided in Example 1 of the present invention;

[0095] Figure 4 A schematic diagram of a method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls provided by the present invention. DETAILED DESCRIPTION

[0096] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0097] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without further purification or treatment.

[0098] Example 1

[0099] like Figure 1 As shown, this embodiment provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof, and the preparation method specifically includes the following steps:

[0100] S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder;

[0101] Specifically, S1: tetraethyl orthosilicate and anhydrous ethanol are mixed in a volume ratio of 1:3.4, and then deionized water and 0.2M ammonia water are added to obtain solution A, wherein the molar ratio of water to tetraethyl orthosilicate is 2:1, and ammonia water is added to adjust the pH to 8. After stirring at room temperature for 1.2 hours, the temperature is raised to 45°C, and a mixed modifier is added dropwise at a dropping rate of 2 mL / min to obtain a reaction solution B, wherein the volume ratio of hexamethyldisilazane / chloromethyltrimethylsilane in the mixed modifier is 1:1, and the molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.2:1. After stirring for 4 hours, the mixture is aged at room temperature for 24 hours to obtain a gel, and after alcohol gel exchange, the mixture is supercritically dried to obtain a hydrophobically modified silica aerogel, and the modified silica aerogel powder is pulverized; Figure 1 From its scanning electron microscope image, it can be observed that the silica aerogel is constructed of a large number of nano-scale particles with a relatively uniform particle size distribution. A rich interconnected pore network is formed between the particles. The sample shows good structural integrity and uniformity. This microstructure is conducive to achieving excellent thermal insulation performance.

[0102] S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers;

[0103] Specifically, S2: potassium titanate nanofibers and Tris buffer were mixed at a mass ratio of 1:200, and dopamine hydrochloride was added to obtain a reaction solution C, wherein the mass ratio of potassium titanate fiber to dopamine hydrochloride was 2.5:1, and the mixture was stirred at room temperature for 5.6 hours, filtered, and washed to obtain a precipitate D, which was dispersed in deionized water, and a polyacrylic acid aqueous solution with a mass fraction of 5 wt.% was added to obtain a reaction solution E, wherein the mass ratio of polyacrylic acid to precipitate D was 0.4:1, and the mixture was stirred at a constant temperature of 65°C for 3.4 hours, and the mixture was centrifuged and vacuum dried to obtain modified potassium titanate;

[0104] S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles;

[0105] Specifically, S3: treating tungsten carbide nanoparticles in a plasma device to obtain activated tungsten carbide nanoparticles, dispersing the activated tungsten carbide nanoparticles in a 1M hydrochloric acid solution at a mass ratio of 1:200, adding aniline under ice bath conditions to obtain a reaction solution F, wherein the mass ratio of activated tungsten carbide nanoparticles to aniline is 2:1, and after stirring, adding a 1M ammonium persulfate solution at a dropping speed of 2 mL / min to obtain a reaction solution G, wherein the molar ratio of ammonium persulfate to aniline is 1.2:1, reacting at a low temperature of 4°C for 3h, centrifuging, washing, and vacuum drying to obtain modified tungsten carbide; Figure 2The high-resolution transmission electron microscope image shows that the modified particles present a typical core-shell structure, in which the darker core area is the tungsten carbide nanoparticles, surrounded by the lighter polyaniline coating layer. The particles as a whole present a nearly spherical morphology, and the polyaniline coating layer is evenly distributed on the surface of the tungsten carbide particles, forming a continuous and complete shell structure.

[0106] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets;

[0107] Specifically, S4: ball-milling boron nitride nanosheets to obtain activated boron nitride nanosheets, mixing the activated boron nitride nanosheets / N,N-dimethylformamide dispersion with a 2 mg / mL graphene oxide dispersion to obtain a reaction solution H, wherein the mass ratio of the activated boron nitride nanosheets / N,N-dimethylformamide dispersion is 1:150, and the mass ratio of graphene oxide to the activated boron nitride nanosheets is 0.2:1, adding ascorbic acid to obtain a reaction solution I, wherein the mass ratio of graphene oxide to ascorbic acid is 1:3, reacting in a water bath at a constant temperature of 75°C for 4 hours, filtering, washing, and vacuum drying to obtain modified boron nitride; Figure 3 From the scanning electron microscope image, it can be observed that the modified boron nitride presents typical two-dimensional layered structural characteristics. After ball milling activation and graphene oxide composite modification, the sample formed an obvious multi-level wrinkled sheet structure. A staggered three-dimensional network structure was formed between the sheets, and the interlayer spacing was significantly increased, indicating that graphene oxide was successfully inserted into the interlayer of boron nitride.

[0108] S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution for reaction, then adding γ-aminopropyl polydimethylsiloxane for reaction, adding tetrahydrofuran for dilution, and then rotary evaporating to obtain a silicone-modified epoxy resin;

[0109] Specifically, S5: mixing bisphenol A epoxy resin with a toluene / tetrahydrofuran mixed solution to obtain a resin dispersion, wherein the volume ratio of toluene to tetrahydrofuran is 3:1, and the mass fraction of bisphenol A epoxy resin in the resin dispersion is 40wt.%, and after stirring, adding a 34wt% γ-aminopropyl polydimethylsiloxane / toluene solution to obtain a reaction solution J, wherein the molar ratio of bisphenol A epoxy resin to γ-aminopropyl polydimethylsiloxane is 3:1, stirring and reacting at a constant temperature of 89° C. under nitrogen protection for 3.4 hours, and then cooling to room temperature, and then adding tetrahydrofuran to dilute to obtain a solution K, wherein the mass fraction of tetrahydrofuran in the solution K is 30wt.%, filtering, and rotary evaporation to obtain a silicone-modified epoxy resin;

[0110] S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

[0111] Specifically, S6: Disperse modified potassium titanate, modified tungsten carbide, and modified boron nitride in anhydrous ethanol at a mass ratio of 1:40 and mix them evenly, add silicone-modified epoxy resin to obtain a base liquid, disperse at a high speed of 4000 rpm for 30 minutes, then add modified silica aerogel powder, and then add carbon fiber and BYK-W966, BYK-035, BYK-358, 288 to obtain the pre-treated coating liquid, vacuum degassing and then adding EC 301 obtains an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls; the mass ratio of modified potassium titanate, modified tungsten carbide, modified boron nitride, silicone-modified epoxy resin, modified silica aerogel powder, carbon fiber, additives and curing agent is 5:3:4:100:30:8:6:12; the mass ratio of dispersant, defoamer, leveling agent and thickener is 2:1:1:3.

[0112] Example 2

[0113] This embodiment provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof, the preparation method specifically comprising the following steps:

[0114] S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder;

[0115] Specifically, S1: tetraethyl orthosilicate and anhydrous ethanol are mixed in a volume ratio of 1:3, and then deionized water and 0.3M ammonia water are added to obtain solution A, wherein the molar ratio of water to tetraethyl orthosilicate is 2.5:1, and ammonia water is added to adjust the pH to 9. After stirring at room temperature for 1.6 hours, the temperature is raised to 50°C, and a mixed modifier is added dropwise at a dropping rate of 1 mL / min to obtain a reaction solution B, wherein the volume ratio of hexamethyldisilazane / chloromethyltrimethylsilane in the mixed modifier is 1.4:1, and the molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.3:1. After stirring for 5 hours, the mixture is aged at room temperature for 32 hours to obtain a gel, and after alcohol gel exchange, the mixture is supercritically dried to obtain a hydrophobically modified silica aerogel, and the modified silica aerogel powder is pulverized;

[0116] S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers;

[0117] Specifically, S2: potassium titanate nanofibers and Tris buffer were mixed at a mass ratio of 1:220, and then dopamine hydrochloride was added to obtain a reaction solution C, wherein the mass ratio of potassium titanate fiber to dopamine hydrochloride was 2.6:1, and the mixture was stirred at room temperature for 5 hours, filtered, and washed to obtain a precipitate D, which was dispersed in deionized water, and a polyacrylic acid aqueous solution with a mass fraction of 5.3wt.% was added to obtain a reaction solution E, wherein the mass ratio of polyacrylic acid to precipitate D was 0.3:1, and the mixture was stirred at a constant temperature of 55°C for 4 hours, and the mixture was centrifuged and vacuum dried to obtain modified potassium titanate;

[0118] S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles;

[0119] Specifically, S3: treating tungsten carbide nanoparticles in a plasma device to obtain activated tungsten carbide nanoparticles, dispersing the activated tungsten carbide nanoparticles in a 1.7M hydrochloric acid solution at a mass ratio of 1:230, adding aniline under ice bath conditions to obtain a reaction solution F, wherein the mass ratio of activated tungsten carbide nanoparticles to aniline is 2.2:1, and after stirring, adding a 1.7M ammonium persulfate solution at a dropping speed of 1.8mL / min to obtain a reaction solution G, wherein the molar ratio of ammonium persulfate to aniline is 1.3:1, reacting at a low temperature of 2°C for 4h, centrifuging, washing, and vacuum drying to obtain modified tungsten carbide;

[0120] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets;

[0121] Specifically, S4: ball-milling boron nitride nanosheets to obtain activated boron nitride nanosheets, mixing the activated boron nitride nanosheets / N,N-dimethylformamide dispersion with a 2.5 mg / mL graphene oxide dispersion to obtain a reaction solution H, wherein the mass ratio of the activated boron nitride nanosheets / N,N-dimethylformamide dispersion is 1:200, and the mass ratio of graphene oxide to the activated boron nitride nanosheets is 0.24:1, adding ascorbic acid to obtain a reaction solution I, wherein the mass ratio of graphene oxide to ascorbic acid is 1:3.5, reacting in a water bath at a constant temperature of 80°C for 3.4 hours, filtering, washing, and vacuum drying to obtain modified boron nitride;

[0122] S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution for reaction, then adding γ-aminopropyl polydimethylsiloxane for reaction, adding tetrahydrofuran for dilution, and then rotary evaporating to obtain a silicone-modified epoxy resin;

[0123] Specifically, S5: mixing bisphenol A epoxy resin with a toluene / tetrahydrofuran mixed solution to obtain a resin dispersion, wherein the volume ratio of toluene to tetrahydrofuran is 3.6:1, and the mass fraction of bisphenol A epoxy resin in the resin dispersion is 50wt.%, and after stirring, adding a 30wt% γ-aminopropyl polydimethylsiloxane / toluene solution to obtain a reaction solution J, wherein the molar ratio of bisphenol A epoxy resin to γ-aminopropyl polydimethylsiloxane is 2:1, stirring and reacting at a constant temperature of 80°C under nitrogen protection for 3.7h, and then cooling to room temperature, and then adding tetrahydrofuran to dilute to obtain a solution K, wherein the mass fraction of tetrahydrofuran in the solution K is 32wt.%, filtering, and rotary evaporation to obtain a silicone-modified epoxy resin;

[0124] S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

[0125] Specifically, S6: modified potassium titanate, modified tungsten carbide, and modified boron nitride are dispersed in anhydrous ethanol at a mass ratio of 1:44 and mixed evenly, silicone-modified epoxy resin is added to obtain a base liquid, and modified silica aerogel powder is added after high-speed dispersion at a speed of 3000 rpm for 20 minutes, followed by carbon fiber and BYK-378, BYK-066N, BYK-333, and BYK-425 to obtain a pre-treated coating liquid, and EPIKURE is added after vacuum degassing. TM 3253 An aerogel-based thermal insulation and waterproof composite coating material for building exterior walls is obtained; wherein the mass ratio of modified potassium titanate, modified tungsten carbide, modified boron nitride, organosilicon-modified epoxy resin, modified silica aerogel powder, carbon fiber, additive and curing agent is 6:4:5:100:35:12:7:13; the mass ratio of dispersant, defoamer, leveling agent and thickener is 2.4:1.3:1.5:2.4.

[0126] Example 3

[0127] This embodiment provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof, the preparation method specifically comprising the following steps:

[0128] S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder;

[0129] Specifically, S1: tetraethyl orthosilicate and anhydrous ethanol are mixed in a volume ratio of 1:4, and then deionized water and 0.26M ammonia water are added to obtain solution A, wherein the molar ratio of water to tetraethyl orthosilicate is 2.7:1, and ammonia water is added to adjust the pH to 8.6. After stirring at room temperature for 1 hour, the temperature is raised to 48°C, and a mixed modifier is added dropwise at a dropping rate of 1.4 mL / min to obtain a reaction solution B, wherein the volume ratio of hexamethyldisilazane / chloromethyltrimethylsilane in the mixed modifier is 1.7:1, and the molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.23:1. After stirring for 5.4 hours, the mixture is aged at room temperature for 40 hours to obtain a gel, and after alcohol gel exchange, the mixture is supercritically dried to obtain a hydrophobically modified silica aerogel, and the modified silica aerogel powder is pulverized;

[0130] S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers;

[0131] Specifically, S2: potassium titanate nanofibers and Tris buffer were mixed at a mass ratio of 1:230, and then dopamine hydrochloride was added to obtain a reaction solution C, wherein the mass ratio of potassium titanate fiber to dopamine hydrochloride was 2.8:1, and the mixture was stirred at room temperature for 6 hours, filtered, and washed to obtain a precipitate D, which was dispersed in deionized water, and a polyacrylic acid aqueous solution with a mass fraction of 5.7wt.% was added to obtain a reaction solution E, wherein the mass ratio of polyacrylic acid to precipitate D was 0.34:1, and the mixture was stirred at a constant temperature of 58°C for 3 hours, and the mixture was centrifuged and vacuum dried to obtain modified potassium titanate;

[0132] S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles;

[0133] Specifically, S3: treating tungsten carbide nanoparticles in a plasma device to obtain activated tungsten carbide nanoparticles, dispersing the activated tungsten carbide nanoparticles in a 1.9M hydrochloric acid solution at a mass ratio of 1:240, adding aniline under ice bath conditions to obtain a reaction solution F, wherein the mass ratio of activated tungsten carbide nanoparticles to aniline is 2.4:1, and after stirring, adding a 2M ammonium persulfate solution at a dropping speed of 1.2 mL / min to obtain a reaction solution G, wherein the molar ratio of ammonium persulfate to aniline is 1.4:1, reacting at a low temperature of 3°C for 3.6 hours, centrifuging, washing, and vacuum drying to obtain modified tungsten carbide;

[0134] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets;

[0135] Specifically, S4: ball-milling boron nitride nanosheets to obtain activated boron nitride nanosheets, mixing the activated boron nitride nanosheets / N,N-dimethylformamide dispersion with a graphene oxide dispersion having a concentration of 2.8 mg / mL to obtain a reaction solution H, wherein the mass ratio of the activated boron nitride nanosheets / N,N-dimethylformamide dispersion is 1:170, and the mass ratio of graphene oxide to the activated boron nitride nanosheets is 0.3:1, adding ascorbic acid to obtain a reaction solution I, wherein the mass ratio of graphene oxide to ascorbic acid is 1:3.7, reacting in a water bath at a constant temperature of 85°C for 3h, filtering, washing, and vacuum drying to obtain modified boron nitride;

[0136] S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution for reaction, then adding γ-aminopropyl polydimethylsiloxane for reaction, adding tetrahydrofuran for dilution, and then rotary evaporating to obtain a silicone-modified epoxy resin;

[0137] Specifically, S5: mixing bisphenol A epoxy resin with a toluene / tetrahydrofuran mixed solution to obtain a resin dispersion, wherein the volume ratio of toluene to tetrahydrofuran is 4:1, and the mass fraction of bisphenol A epoxy resin in the resin dispersion is 45wt.%, and after stirring, adding a 37wt% γ-aminopropyl polydimethylsiloxane / toluene solution to obtain a reaction solution J, wherein the molar ratio of bisphenol A epoxy resin to γ-aminopropyl polydimethylsiloxane is 2.5:1, stirring and reacting at a constant temperature of 84°C under nitrogen protection for 3h, and then cooling to room temperature, and then adding tetrahydrofuran to dilute to obtain a solution K, wherein the mass fraction of tetrahydrofuran in the solution K is 34wt.%, filtering, and rotary evaporation to obtain a silicone-modified epoxy resin;

[0138] S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

[0139] Specifically, S6: modified potassium titanate, modified tungsten carbide, and modified boron nitride are dispersed in anhydrous ethanol at a mass ratio of 1:47 and mixed evenly, silicone-modified epoxy resin is added to obtain a base liquid, and the base liquid is dispersed at a high speed of 3400 rpm for 23 min, and then modified silica aerogel powder is added, followed by carbon fiber and BYK-W966, BYK-066N, BYK-358, and BYK-425 to obtain a pre-treated coating liquid, and then vacuum degassing is added. EC 301 obtained an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls; the mass ratio of modified potassium titanate, modified tungsten carbide, modified boron nitride, silicone-modified epoxy resin, modified silica aerogel powder, carbon fiber, additives and curing agent was 7:4.6:6:100:38:10:8:14; the mass ratio of dispersant, defoamer, leveling agent and thickener was 2.7:1.4:1.4:2.5.

[0140] Example 4

[0141] This embodiment provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls and a preparation method thereof, the preparation method specifically comprising the following steps:

[0142] S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder;

[0143] Specifically, S1: tetraethyl orthosilicate and anhydrous ethanol are mixed in a volume ratio of 1:3.6, and then deionized water and 0.28M ammonia water are added to obtain solution A, wherein the molar ratio of water to tetraethyl orthosilicate is 3:1, and ammonia water is added to adjust the pH to 8.3. After stirring at room temperature for 2 hours, the temperature is raised to 47°C, and a mixed modifier is added dropwise at a dropping rate of 1.8 mL / min to obtain a reaction solution B, wherein the volume ratio of hexamethyldisilazane / chloromethyltrimethylsilane in the mixed modifier is 2:1, and the molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.27:1. After stirring for 6 hours, the mixture is aged at room temperature for 48 hours to obtain a gel, and after alcohol gel exchange, the mixture is supercritically dried to obtain a hydrophobically modified silica aerogel, and the modified silica aerogel powder is pulverized;

[0144] S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers;

[0145] Specifically, S2: potassium titanate nanofibers and Tris buffer were mixed at a mass ratio of 1:250, and then dopamine hydrochloride was added to obtain a reaction solution C, wherein the mass ratio of potassium titanate fiber to dopamine hydrochloride was 3:1, and the mixture was stirred at room temperature for 5.8 hours, filtered, and washed to obtain a precipitate D, which was dispersed in deionized water, and a polyacrylic acid aqueous solution with a mass fraction of 6 wt.% was added to obtain a reaction solution E, wherein the mass ratio of polyacrylic acid to precipitate D was 0.37:1, and the mixture was stirred at a constant temperature of 62°C for 3.7 hours, and the mixture was centrifuged and vacuum dried to obtain modified potassium titanate;

[0146] S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles;

[0147] Specifically, S3: treating tungsten carbide nanoparticles in a plasma device to obtain activated tungsten carbide nanoparticles, dispersing the activated tungsten carbide nanoparticles in a 2M hydrochloric acid solution at a mass ratio of 1:250, adding aniline under ice bath conditions to obtain a reaction solution F, wherein the mass ratio of activated tungsten carbide nanoparticles to aniline is 2.5:1, and after stirring, adding a 1.5M ammonium persulfate solution at a dropping speed of 1 mL / min to obtain a reaction solution G, wherein the molar ratio of ammonium persulfate to aniline is 1.32:1, reacting at a low temperature of 3.4°C for 3.8 hours, centrifuging, washing, and vacuum drying to obtain modified tungsten carbide;

[0148] S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets;

[0149] Specifically, S4: ball-milling boron nitride nanosheets to obtain activated boron nitride nanosheets, mixing the activated boron nitride nanosheets / N,N-dimethylformamide dispersion with a 3 mg / mL graphene oxide dispersion to obtain a reaction solution H, wherein the mass ratio of the activated boron nitride nanosheets / N,N-dimethylformamide dispersion is 1:190, and the mass ratio of graphene oxide to activated boron nitride nanosheets is 0.27:1, adding ascorbic acid to obtain a reaction solution I, wherein the mass ratio of graphene oxide to ascorbic acid is 1:4, reacting in a water bath at a constant temperature of 82°C for 3.7 hours, filtering, washing, and vacuum drying to obtain modified boron nitride;

[0150] S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution for reaction, then adding γ-aminopropyl polydimethylsiloxane for reaction, adding tetrahydrofuran for dilution, and then rotary evaporating to obtain a silicone-modified epoxy resin;

[0151] Specifically, S5: mixing bisphenol A epoxy resin with a toluene / tetrahydrofuran mixed solution to obtain a resin dispersion, wherein the volume ratio of toluene to tetrahydrofuran is 3.8:1, and the mass fraction of bisphenol A epoxy resin in the resin dispersion is 47wt.%, and after stirring, adding a 40wt% γ-aminopropyl polydimethylsiloxane / toluene solution to obtain a reaction solution J, wherein the molar ratio of bisphenol A epoxy resin to γ-aminopropyl polydimethylsiloxane is 2.8:1, stirring and reacting at a constant temperature of 90°C under nitrogen protection for 4 hours, and then cooling to room temperature, and then adding tetrahydrofuran to dilute to obtain a solution K, wherein the mass fraction of tetrahydrofuran in the solution K is 35wt.%, filtering, and rotary evaporation to obtain a silicone-modified epoxy resin;

[0152] S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

[0153] Specifically, S6: modified potassium titanate, modified tungsten carbide, and modified boron nitride are dispersed in anhydrous ethanol at a mass ratio of 1:50 and mixed evenly, silicone-modified epoxy resin is added to obtain a base liquid, and the base liquid is dispersed at a high speed of 3800 rpm for 27 minutes, and then modified silica aerogel powder is added, and then carbon fiber and BYK-378, BYK-035, BYK-333, 288 to obtain the pre-treated coating liquid, vacuum degassing and then adding EPIKURE TM 3253 An aerogel-based thermal insulation and waterproof composite coating material for building exterior walls is obtained; wherein the mass ratio of modified potassium titanate, modified tungsten carbide, modified boron nitride, organosilicon-modified epoxy resin, modified silica aerogel powder, carbon fiber, additive and curing agent is 8:5:7:100:40:11:9:15; the mass ratio of dispersant, defoamer, leveling agent and thickener is 3:1.5:1.2:2.

[0154] Comparative Example 1

[0155] This comparative example provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls, which is different from Example 1 in that in step S1, no mixing modifier is added, and other operating steps and process parameters are exactly the same as those in Example 1.

[0156] Comparative Example 2

[0157] This comparative example provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls. The difference from Example 1 is that step S2 is omitted, and the other operating steps and process parameters are exactly the same as those of Example 1.

[0158] Comparative Example 3

[0159] This comparative example provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls. The difference from Example 1 is that step S4 is omitted, and the other operating steps and process parameters are exactly the same as those of Example 1.

[0160] Comparative Example 4

[0161] This comparative example provides an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls. The difference from Example 1 is that step S5 is omitted, and the other operating steps and process parameters are exactly the same as those of Example 1.

[0162] The performance test of the aerogel-based thermal insulation and waterproof composite coating materials for building exterior walls of the above-mentioned Examples 1-4 and Comparative Examples 1-4 was carried out, and the specific process is as follows:

[0163] Test the thermal conductivity of the sample according to GB / T 10294-2008;

[0164] The contact angles of the coating surfaces of Examples 1-4 and Comparative Examples 1-4 were tested by an optical contact angle tester: the contact angles of 5 points randomly collected from the test sample surface were averaged using 5 μL of deionized water to obtain the average contact angle value of the sample;

[0165] The test results are shown in Table 1.

[0166] Table 1: Performance test results of aerogel-based thermal insulation and waterproof composite coating materials for building exterior walls of Examples 1-4 and Comparative Examples 1-4

[0167]

[0168] From the test results of Example 1 and Comparative Example 1, it can be obtained that when the silica surface is treated without using a mixed modifier, its thermal conductivity increases from 0.034W / (m·K) to 0.058W / (m·K), and the contact angle drops sharply from 153° to 92°. This is because there are a large number of Si-OH groups on the surface of the unmodified aerogel, and the surface energy is significantly increased, resulting in enhanced hydrophilicity. These exposed hydroxyl groups will continuously absorb moisture in the environment, causing partial pore structure collapse and microstructural destruction, forming a wider heat conduction path, and ultimately resulting in a decrease in the thermal insulation performance of the coating. At the same time, the increase in surface energy makes the coating almost lose its waterproof performance. Even with the presence of modified epoxy resin and other modified fillers, it still cannot meet the waterproof requirements in practical applications.

[0169] From the test results of Example 1 and Comparative Example 2, it can be seen that when potassium titanate is not modified with dopamine and polyacrylic acid, its thermal conductivity increases from 0.034W / (m·K) to 0.042W / (m·K), and the contact angle slightly decreases from 153° to 150°. This is mainly because the dispersibility of unmodified potassium titanate in the organic matrix is ​​reduced, and the interface bonding with the matrix is ​​weakened, resulting in changes in the local thermal network structure, thereby reducing the thermal insulation performance of the coating; but because the main hydrophobic structure is still intact and the synergistic effect of other components, the waterproof performance of the coating is less affected.

[0170] From the test results of Example 1 and Comparative Example 3, it can be seen that when the boron nitride nanosheets are not ball-milled and activated and modified with graphene oxide, the thermal conductivity increases from 0.034W / (m·K) to 0.045W / (m·K), and the contact angle decreases from 153° to 142°. This is because the dispersibility of the unmodified boron nitride flakes decreases, and local agglomerations are easily formed in the matrix, resulting in uneven heat conduction paths and reduced uniformity of the insulation layer structure, thereby moderately reducing the insulation effect of the coating; at the same time, due to the uneven distribution of the flakes, the surface roughness distribution changes, and the multi-level structure is partially missing, which slightly reduces its waterproof performance, but the basic hydrophobic performance is still maintained.

[0171] From the test results of Example 1 and Comparative Example 4, it can be obtained that when the bisphenol A epoxy resin is modified without introducing silicone, the thermal conductivity coefficient increases significantly from 0.034W / (m·K) to 0.054W / (m·K), and the contact angle decreases sharply from 153° to 89°. This is because the epoxy resin, as a matrix material, is a continuous phase that determines the basic properties of the composite material. The exposure of a large number of -OH groups on the molecular chain of the unmodified epoxy resin leads to a significant increase in surface energy, while affecting the dispersion state of the filler and the formation of the interface structure. Due to the hydrophilicity of the matrix material, the entire hydrophobic network is destroyed, and even the presence of hydrophobic components such as modified aerogels cannot make up for the hydrophilic properties of the matrix material. In addition, the interface bonding between the unmodified epoxy resin and the aerogel deteriorates, the dispersion of the filler decreases, microscopic defects are generated, and an incomplete heat conduction network is formed. These factors together lead to a decrease in the thermal insulation and waterproof properties of the coating.

[0172] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls, characterized in that: The preparation method comprises: S1: adding deionized water and ammonia water to a ethyl orthosilicate / anhydrous ethanol solution and stirring, then adding a mixed modifier to react to obtain a modified sol, dispersing and aging, supercritical drying to obtain a modified silica aerogel, and pulverizing to obtain a modified silica aerogel powder; S2: potassium titanate nanofibers are mixed with Tris buffer and dopamine hydrochloride is added to obtain a first precipitate, which is dispersed in a polyacrylic acid solution to react and obtain modified potassium titanate nanofibers; S3: Treat tungsten carbide with a plasma device to obtain activated tungsten carbide, disperse it in hydrochloric acid, add aniline to react, then add ammonium persulfate solution and react, and filter to obtain modified tungsten carbide nanoparticles; S4: ball-milling the boron nitride nanosheets to obtain activated boron nitride, dispersing the activated boron nitride in N,N-dimethylformamide, adding graphene oxide and ascorbic acid to react, and filtering to obtain modified boron nitride nanosheets; S5: adding bisphenol A epoxy resin to a toluene / tetrahydrofuran solution, adding γ-aminopropyl polydimethylsiloxane to obtain a reaction solution J, reacting under nitrogen protection, then adding tetrahydrofuran to obtain a solution K, and rotary evaporating to obtain a silicone-modified epoxy resin; S6: Disperse modified potassium titanate nanofibers, modified tungsten carbide nanoparticles and modified boron nitride nanosheets in anhydrous ethanol and mix evenly, add silicone-modified epoxy resin and mix evenly to obtain a base liquid; add modified silica aerogel powder and mix evenly, then add carbon fiber and additives, add curing agent after degassing and stir to obtain an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls.

2. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S1: The volume ratio of ethyl orthosilicate to anhydrous ethanol in the ethyl orthosilicate / anhydrous ethanol solution is 1:3-4; The molar ratio of deionized water to tetraethyl orthosilicate is 1.5-2.5:1; The concentration of the ammonia water is 0.2-0.3 M, and the pH value of the solution is adjusted to 8-9 using the ammonia water.

3. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S1: The mixed modifier is a hexamethyldisilazide / chloromethyltrimethylsilane mixed modifier, and the volume ratio of hexamethyldisilazide to chloromethyltrimethylsilane is 1-2:1; The molar ratio of the mixed modifier to tetraethyl orthosilicate is 0.2-0.3:

1.

4. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S2: The mass ratio of the potassium titanate nanofibers to the Tris buffer is 1:200-250; The mass ratio of the potassium titanate nanofibers to dopamine hydrochloride is 2.5-3:1; The mass ratio of the polyacrylic acid to the precipitate D is 0.3-0.4:

1.

5. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S3: The concentration of the hydrochloric acid solution is 1-2M; The mass ratio of the activated tungsten carbide nanoparticles to the hydrochloric acid solution is 1:200-250; The mass ratio of the activated tungsten carbide nanoparticles to aniline is 2-2.5:1; The concentration of the ammonium persulfate solution is 1-2M; The molar ratio of the ammonium persulfate to the aniline is 1.2-1.4:

1.

6. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S4: The mass ratio of the activated boron nitride nanosheets to the N,N-dimethylformamide dispersion is 1:150-200; The mass ratio of the graphene oxide to the activated boron nitride nanosheets is 0.2-0.3:1; The mass ratio of the graphene oxide to ascorbic acid is 1:3-4.

7. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S5: The volume ratio of toluene to tetrahydrofuran in the toluene / tetrahydrofuran mixed solution is 3-4:1; The mass fraction of the bisphenol A epoxy resin in the resin dispersion is 40-50wt.%; The molar ratio of the bisphenol A epoxy resin to the γ-aminopropyl polydimethylsiloxane is 2-3:1; The mass fraction of tetrahydrofuran in the solution K is 30-35 wt.%.

8. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S6: the mass ratio of the mixture of the modified potassium titanate, the modified tungsten carbide and the modified boron nitride to ethanol is 1:40-50.

9. The method for preparing an aerogel-based thermal insulation and waterproof composite coating material for building exterior walls according to claim 1, characterized in that: In S6: The auxiliary agents are dispersants, defoamers, leveling agents and thickeners; The dispersant is BYK-W966 or BYK-378; The defoamer is BYK-066N or BYK-035; The leveling agent is BYK-358 or BYK-333; The thickener is BYK-425 or 288; The curing agent is EC 301 or EPIKURE TM 3253.

10. An aerogel-based thermal insulation and waterproof composite coating material for building exterior walls prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The mass ratio of modified potassium titanate, modified tungsten carbide, modified boron nitride, organosilicon-modified epoxy resin, modified silica aerogel powder, carbon fiber, auxiliary agent and curing agent in the aerogel-based thermal insulation and waterproof composite coating material for building exterior walls is (5-8): (3-5): (4-7): 100: (30-40): (8-12): (6-9): (12-15); Wherein, the auxiliary agent is a dispersant, a defoamer, a leveling agent and a thickener; The mass ratio of the dispersant, the defoamer, the leveling agent and the thickener is (2-3): (1-1.5): (1-1.5): (2-3).

Citation Information

Patent Citations

  • Method for preparing hydrophobic SiO2 aerogel

    CN101503195A

  • Tungsten carbide / conductive polyaniline composite particle and preparation method thereof

    CN101525488A

  • Low thermal conductivity composite thermal insulation paint and preparation method thereof

    CN102367353A

  • Silica aerogel microsphere composite thermal insulation coating

    CN103333542A

  • Modified silicon dioxide aerogel microsphere thermal-insulation coating

    CN104231798A

Cited By

  • Carbon fiber directionally-distributed high-thermal-conductivity sealing paste and preparation method thereof

    CN120518981A

  • Super-thermal-insulation aerogel exterior wall coating and preparation method thereof

    CN120665512A

  • High-temperature-resistant aerogel composite material and preparation method thereof

    CN121063910A

  • High-temperature resistant aerogel composite materials and their preparation methods

    CN121063910B